The Analysis of The Effect of Return of Investment (ROI) on Stock Price and Financial Performance of a Company - Setiawan, Christopher Ari; Tina Rosa (Journal of Accounting, Management, Economics, and Business (ANALYSIS), 2023)
There are many choices of investment instruments that are now available provide more choices for investors. Here are some quite popular investment instruments in Indonesia: Deposits, Gold, Stocks, Property, Stocks, Mutual Funds, and Peer to Peer Lending. Stock is a high-risk investment instrument. Stock are proof of ownership of a company in the capital market. The more shares purchased, the greater the percentage of company ownership obtained. Return on Investment is an important factor where it can be an indicator of a company's financial condition in good condition. One indicator of a good company in managing its finances is by looking at the company's financial performance. This is very important, so that the resources within the company are used optimally in dealing with existing changes and remain in a financially stable condition. This study aims to determine how much influence Return on Investment has on Stock Value and Financial Performance of a company through the results of a synthesis of ten journals themed on Return on Investment analysis in a company that is already listed on the Indonesia Stock Exchange. Return on Investment (ROI) has an influence on the movement of a company's stock price on the Indonesia Stock Exchange. A high ROI value indicates a high stock price in a company. Conversely, a low ROI value indicates that a company's stock price is low. A high ROI value is an indicator of a company having good financial performance, if the ROI value is low, then the company's financial performance is not good.